2017
DOI: 10.1088/1475-7516/2017/02/042
|View full text |Cite
|
Sign up to set email alerts
|

Supernova constraints on massive (pseudo)scalar coupling to neutrinos

Abstract: Abstract. In this paper we derive constraints on the emission of a massive (pseudo)scalar S from annihilation of neutrinos in the core of supernovae through the dimension-4 coupling ννS, as well as the effective dimension-5 operator 1 Λ (νν)(SS). While most of earlier studies have focused on massless or ultralight scalars, our analysis involves scalar with masses of order eV − GeV which can be copiously produced during the explosion of supernovae, whose core temperature is generally of order T ∼ O(10) MeV. Fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 165 publications
3
96
0
Order By: Relevance
“…The analysis of Ref. [26] found that for 1 MeV ≲ m ϕ ≲ 100 MeV, values of λ αβ between 10 −12 to 10 −6 are excluded, for α, β ¼ e, μ. For larger couplings, the ϕ particles are reabsorbed by the supernova and no longer affect its cooling.…”
Section: G Supernova 1987amentioning
confidence: 99%
“…The analysis of Ref. [26] found that for 1 MeV ≲ m ϕ ≲ 100 MeV, values of λ αβ between 10 −12 to 10 −6 are excluded, for α, β ¼ e, μ. For larger couplings, the ϕ particles are reabsorbed by the supernova and no longer affect its cooling.…”
Section: G Supernova 1987amentioning
confidence: 99%
“…The discovery of such a mode would therefore strongly hint at a more complicated majoron realization. Due to the small Jνν coupling, supernova constraints are also easily evaded [105].…”
Section: Jhep05(2017)102mentioning
confidence: 99%
“…For a TeV scale N , the mixing V νN ∼ 10 −6 , and we are then safe from the Majoron limits from supernova observations [65] and other astrophysical and terrestrial constraints [66,67]. Here we assume this to be the case.…”
Section: Global U(1) B−l Modelmentioning
confidence: 99%